NOMINAL AND VERBAL SENTENCE OF SIMPLE PRESENT TENSE ERRORS IN STUDENTS’ DESCRIPTIVE WRITING ABILITY - Viar Dwi Kartika (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study investigated Nominal and Verbal Sentence of Simple Present Tense Errors in Students’ Descriptive Writing Ability in Universitas Catur Insan Cendekia, Cirebon. This study used  Descriptive Qualitative as Method. The writer chose the texts to analyze the data, interpret data, and conclude the result of study from Students’ Descriptive Writing. The findings showed that the total errors in Nominal Sentence is 94, and Misformation is the most used error consisting of 52 errors or 55,31%. Moreover, the total errors in Verbal Sentence is 162, and Misformation is the most frequency consisting of 90 errors or 55,55%. Those errors are affected by lacking knowledge of grammar, especially to form nominal and verbal sentences.